Variation of beam quality correction factor with time: Cases for NE2571 and NE2581 chambers in the 6 and 10 MV x-rays Beams - Samat S.B; Too S.X; Kadni T; Dolah M.T (Universiti Kebangsaan Malaysia, 2009)
The values of beam quality correction factor kQ that were experimentally determined from year 2002 to 2008 were analysed. As kQ is the function of ionization chamber and beam quality, the analysis were based on three cases namely (a) kQ(NE2571, 6 MV x-rays) that were determined from 17 measurements in the duration of 69 months at 6 radiotherapy centres, (b) kQ(NE2571, 10 MV x-rays) from 7 measurements in the duration of 12 months at one radiotherapy centre, and (c) kQ(NE2581, 6 MV x-rays) from 5 measurements in the duration of 5 months also at one radiotherapy centre. The purpose is to examine, in each case, the variation kQ for all the measurements. In other words, to see the variation of kQ with time. Results obtained are 0.993(NE2571, 6 MV), 0.986(NE2571, 10 MV) and 0.986(NE2581, 6 MV). This shows that in each case, despite the difference in the experimental data in getting kQ for all measurement, kQ remains constant with time. Reasons for this are explained.